Item parameter estimations for multidimensional graded response model under complex structures - Kehinde, Olasunkanmi James; Dai, Shenghai; French, Brian (Frontiers in Education, 2022)
Item parameter recovery in the compensatory multidimensional graded response model (MGRM) under simple and complex structures with rating-scale item response data was examined. A simulation study investigated factors that influence the precision of item parameter estimation, including sample size, intercorrelation between the dimensions, and test lengths for the MGRM under balanced and unbalanced complex structures as well as the simple structure. The item responses for the MGRM were generated and analyzed across conditions using the R package mirt. Bias and root mean square error (RMSE) were used to evaluate item parameter recovery. Results suggested that item parameter estimation was more accurate in balanced complex structure conditions than in unbalanced or simple structures, especially when the test length was 40 items, and the sample size was large. Further, the mean bias and RMSE in the recovery of item threshold estimates along the two dimensions for both balanced and unbalanced complex structures were consistent across all conditions.